Peningkatan Penguasaan Kosa Kata Dalam Pembelajaran Bahasa Arab Dengan Penggunaan Media Gambar(Penelitian Tindakan Kelas pada Siswa Kelas VII A Kulliyatul Mu'allimin Al-Islamiyyah Pondok Pesantren Ta'mirul Islam Tegalsari Surakarta Tahun Pelajaran 2015/2016) - Khasanah, Nurrul, Drs. Saifuddin Zuhri, M.Ag (2017)
Image media is an image associated with the subject matter that serves to send a message from the teacher to the student. The success of a learning process can not be separated from the role of the media in it, because the tools or media education is an integral part of the educational process at school. At Ta'mirul Islam Boarding School, the students' mastery of Arabic vocabulary are still less effective and have not been able to take advantage of learning media well and still use conventional ways so that their interest in the Arabic language being reduced. This requires teachers to be more creative with the use of methods that can attract learners. In this study, a problem is how the image media is used to improve the mastery of Arabic vocabulary in class VII A of KMI Surakarta Ta'mirul Islam Boarding School in the 2015/2016 academic school year. The purpose of this study is to describe the use of image media in increasing mastery of the Arabic vocabulary for students of class VII A of KMI Surakarta Ta'mirul Islam Boarding School. The research benefits for students are: to improve the Arabic ability of class VII A of KMI Surakarta Ta'mirul Islam Boarding School while the benefits for teachers are to improve skills in using of appropriate methods in the learning process and to improve skills in the selection of instructional media more effective. This research is a classroom action research with qualitative approach. Methods of data collection use tests, interviews, observation and documentation. Data analysis using quantitative analysis techniques use an interactive model that has three components: data reduction, data presentation and conclusion drawing. Based on the results of this research, it is found that the use of image media can improve the mastery of Arabic vocabulary in class VII A KMI. Increased success of Arabic students shown by the average value of each cycle. The first cycle obtains an average Arabic value of 60.17, the second cycle obtains an average value of 69.29, while the third cycle obtains an average Arabic value of 75.78. The steps of using image media in improving mastery of Arabic Vocabulary are as follows: 1) The teacher gives a picture of the vocabulary he wants to teach and students guess the picture; 2) Teachers provide vocabulary in Arabic; 3) Students imitates the teacher; 4) Students memorize new vocabulary; 5) Students create an example sentence of new vocabulary; 6) The teacher corrects the true/false of students example sentences.